Recent drying technologies used for drying poultry litter (principles, advantages and disadvantages): A comprehensive review - Mehdi Khodadadi; Aminolah Masoumi (Poultry Science)
Wet poultry litter creates an environment that accelerates the growth of bacteria and pathogens, leading to increased ammonia release. A practical way to reduce these adverse effects is heat treatment (drying). This work evaluated different methods for poultry litter drying and presented their principles, advantages, and disadvantages. Oven dryers are not recommended for continual drying due to their low energy efficiency, but decreasing water activity can prevent microbial growth. Rotary dryers provide homogeneous drying, but they are not suitable for drying fragile materials. Freeze drying preserves heat-sensitive ingredients, but the drying duration is high and classified as a high-cost drying technique. Microwave drying technology surpasses conventional methods in achieving both high product quality and energy efficiency. Solar drying emerges as the most economically viable, practical, and environmentally sound method for poultry litter desiccation. However, improperly controlled mass and heat transfer throughout the drying process can compromise product integrity. The use of combined dryers has not been thoroughly evaluated, although they may be more effective due to their synergistic results. This study is helpful for researchers who aim to reduce the adverse effects of poultry litter and manage it more effectively using heat treatment methods.